Insights from the Antidepressant BRITE-MD Trial: Predicting Response - Vinall, Maria (MD Conference Express, 2008)
Results from the Rapid Identification of Treatment Effectiveness in Major Depression [BRITE-MD] study suggest that the use of frontal quantitative EEG could be used as a biomarker to predict treatment outcome with the antidepressant escitalopram.